Entrepreneurship Building Based on Pancasila Values for Push Social Justice Among Generation Z - ita ita yunita; Jamilah Jamilah; Toto Toto Suryadi (Universitas Negeri Surabaya, 2025)
Generation Z has strategic potential as a driving force for entrepreneurship amidst the dynamics of the digital economy and the challenges of social inequality. However, solely profit-oriented entrepreneurship development risks neglecting the dimensions of values and social justice. Therefore, an entrepreneurship building approach is needed that not only fosters business competency but also internalizes the values of Pancasila, particularly the fifth principle, Social Justice for All Indonesians. This study aims to analyze the role of Pancasila-based entrepreneurship building in fostering awareness and practice of social justice among Generation Z. This study uses a qualitative approach with library research methods and conceptual analysis of literature on entrepreneurship, character education, and Pancasila values. The results of the study indicate that Pancasila-based entrepreneurship building contributes to shaping the entrepreneurial mindset of Generation Z that is inclusive, ethical, and oriented towards equitable distribution of economic benefits. The integration of social justice values in entrepreneurship education encourages the emergence of young entrepreneurs who are not only innovative and independent, but also have a concern for the common welfare and reducing social inequality. Pancasila-based entrepreneurship building is an important strategy in developing equitable and sustainable entrepreneurship among Generation Z.